سنن الترمذی پر علماء بنوری ٹاؤن کی خدمات: The efforts of the Scholars of Binnori Town on the Sunan of Imam Tirmizi (Khairulummah, 2022)
Sunan Tirmizi is a hadith, fiqh in light of schools of thought, and ‘ilal hadith collection, which is included within the 6 main books of ahadith. The number of praises sung for the book, is also the amount of services offered to the book. Within these, is the commentaries on Sunan Tirmizi, such as ‘Aridat al-Ahwazi for Ibn al-‘Arabi al-Maliki and Tuhfat al-Ahwazi for Abd al-Rahman al-mubarakfuri. However, these commentaries do no not quench the thirst of the faqih, and have plentiful objections upon the ahnaf. For the necessity of these objections to be answered, Ma’arif al-Sunan was written, by Maulana Yusuf Banuri. This book has, alongside it’s corrections on ‘Aridat al-Ahwazi, many other specialities. The author has expressed his teacher’s [Maulana Anwar Shah al-Kashmiri] views in a sophisticated manner, alongside providing sufficient explanation to any ambiguity found in al-‘Arf al-Shazi. He has also answered objections on the ahnaf, delved into discussions regarding the chain of narration, provided a conclusive opinion on masail with many opinions, entertained discussions on language and theology, listed the opinions of the predecessors and successors, given biographies on some companions and predecessors and some important books and relied solely upon primary sources when relating the opinion of another school of thought. He also draws mainly on what was opined by processors within the ahnaf in their books, and only quotes those scholars who are well grounded, and are a consensually relied upon figure within the academic circles. Thus, after also quoting from ahnaf books of legal verdict, and their commentaries, including many other scholarly books, he provides critical comments on what he has quoted.
Keywords: Sunan Tirmizi; hadith, fiqh; schools of thought; Aridat al-Ahwazi